2000
DOI: 10.3109/10428190009060336
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Primary Adrenal Non-Hodgkin's Lymphoma Associated with Adrenal Insufficiency

Abstract: We report a case of primary adrenal NHL associated with adrenal insufficiency which was successfully treated with steroid replacement and chemotherapy. A 69-year-old woman hospitalized with fatigue and weight loss developed shock and recovered with steroid therapy. Adrenal insufficiency was confirmed by an elevated plasma adrenocorticotropic hormone level and low cortisol. Computed tomography revealed large bilateral adrenal masses. Needle biopsy showed a diffuse, mixed B cell lymphoma. CHOP therapy accompanie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…Bilateral adrenal involvement of PAL is frequently accompanied by clinical adrenal insufficiency [3,4,17-22]. In our series, clinically definite adrenal insufficiency was seen in only one of the five cases in whom the adrenal function was examined.…”
Section: Discussionmentioning
confidence: 47%
“…Bilateral adrenal involvement of PAL is frequently accompanied by clinical adrenal insufficiency [3,4,17-22]. In our series, clinically definite adrenal insufficiency was seen in only one of the five cases in whom the adrenal function was examined.…”
Section: Discussionmentioning
confidence: 47%
“…Thus, we concluded that the current case is histologically diagnosed as primary adrenal DLBCL. In recent cases, (R)-CHOP has been the standard treatment as performed in this case (23)(24)(25). A poor prognosis is thought to be due to advanced age at diagnosis, large tumor size, increased LDH levels, and adrenal insufficiency at the time of presentation, indicating extensive adrenal destruction (7).…”
Section: A) B)mentioning
confidence: 99%
“…One study reported that mean overall-survival rate is 15.3 months; 34 months of the patients who achieve a partial or complete remission after chemotherapy and 3.6 months of the patients who have no response to chemotherapy [8]. The longest survival was 50 months in cases of treating with CHOP chemotherapy [13]. rubicin, prednisone, methotrexate, bleomycin) [9].…”
Section: Discussionmentioning
confidence: 99%
“…Primary malignant lymphomas arising in endocrine organs are rare with representing only 3% of extranodal lymphomas [8]. They are almost confined to the thyroid gland [5,12] Adrenal insufficiency is rare because it becomes apparent when approximately 90% of adrenal cortex is destructed [13]. And most of adrenal insufficiency are believed to be associated with atrophy of adrenal glands, secondary to autoimmune mechanisms [14].…”
Section: Discussionmentioning
confidence: 99%